Pemodelan Sistem Pakar Diagnosis Penyakit pada Sistem Endokrin Manusia dengan Metode Dempster-Shafer - Didin Wahyu Utomo; Suprapto Suprapto; Nurul Hidayat (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The endocrine system is a gland system that acts on the human body whose secretedness called as hormones. Hormones are chemicals which carried within the bloodstream to tissues and organs and then stimulate hormones to perform certain actions. Hormones work directly into the blood without going through the ductus. Endocrine disease is very dangerous and can even lead to death if it were not treated immediately. In the BPJS system that implemented by the Indonesian government, general practitioners serve as the main gateway in diagnosing the disease or determining whether to be referred to a specialist. In the case of endocrine disease patients, it is very dangerous if not treated early, whereas referral process to a specialist or hospital takes a long time due to many patients who come. The purpose of this modelling system is one way done that aims to provide early help for patients with endocrine diseases. This application is developed by using PHP programming language using CodeIgniter framework and MySQL database. The process of calculating the diagnosis of disease using the Dempster-Shafer method. Testing is done by comparing the conformity of results between the diagnosis of the system and the results of expert diagnosis. Based on 35 tested data, obtained 91.428% test accuracy level indicating that modeling expert system diagnosis of endocrine disease with dempster-shafer method can well functioned